Authenticity in the Arabic Classroom: Evaluating Realia’s Effect on Speaking Proficiency - Yunita Indahwati; Ali Maksum; Umihani Umihani (Lingu, 2025)
Purpose – This study addresses the persistent challenge of developing Arabic speaking proficiency (maharah kalām) among junior secondary students, who often lack confidence and fluency due to limited authentic practice. The purpose was to empirically evaluate the effectiveness of realia-based instruction as a practical pedagogical intervention to bridge the gap between classroom learning and real-world communication, arguing that tangible, context-rich materials significantly enhance oral skills. Design/methods/approach – A quasi-experimental, non-equivalent control group design with pre-test and post-test measures was implemented. The study involved 55 seventh-grade students at an Indonesian state Islamic junior high school, with an experimental group (n=31) receiving realia-based instruction and a control group (n=24) receiving conventional instruction over a three-week period. Student speaking performance was quantitatively assessed using a standardized oral rubric before and after the intervention. Findings – The findings revealed a statistically significant and substantial improvement in the experimental group's speaking performance. The post-test mean score for the experimental group (M=50.32, SD=14.05) was significantly higher than that of the control group (M=29.17, SD=4.44). An independent samples t-test confirmed this advantage (t(53)=7.09,p<.001), indicating a large effect size (Hedges’ g=1.90), providing strong evidence that realia-based instruction is more effective than conventional methods. Research implications – The primary implication is pedagogical: integrating realia offers a practical, low-cost strategy for language teachers to create authentic communicative contexts, thereby enhancing student oral proficiency. However, the findings' generalizability is constrained by the study's single-site setting, non-randomized allocation of participants, and the short duration of the intervention. These limitations highlight the need for future research, such as multi-site randomized controlled trials, to validate these results across diverse contexts and assess long-term retention.